Perancangan Storage box Sebagai Media Penyimpanan Ikan Untuk Nelayan Tradisional - Hery Sunarsono; Sadiq Ardo Wibowo (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The economic life of Abang Island, Batam City has considerable potential, the majority of the population works as traditional fishermen who are only supported by catches obtained by fishing or fishing at locations tens of kilometers from the coast. In order to ensure that the quality of the fish caught and its freshness is maintained, the fishermen must freeze it as soon as possible and store it in a cold storage box. This research will provide a solution for traditional fishermen to use storage boxes with better cooling quality than the storage boxes used today by providing an insulator that considers the optimal distance to reduce the conduction process and heat radiation. The purpose of the study was to determine the optimal use of the conduction process and heat radiation in the storage box and to determine the use of coconut fiber as an insulator for fish storage boxes and to find the best composition of coconut fiber and tube ice in the cooling process. The method used is an experimental method by involving fishermen in discussions to design and assemble a storage box made of styrofoam measuring 75 cm long, 42 cm wide, 32 cm high, with coconut fiber as an insulator on the inside of styrofoam, for insulation assistance using an infraboard sheet made of of plastic material measuring 3 mm. Based on the results of the study, it was obtained that the thermal conductivity value using coconut fiber was 0.011 J/sKm, and without using coconut fiber was 0.01 J/sKm, the radiation value was 0.0062, so from the results of the study coconut fiber was very well used as an insulator in inhibitor of the rate of change of room temperature.